Dioctanoyl Ultrashort Tetrabasic β-Peptides Sensitize Multidrug-Resistant Gram-Negative Bacteria to Novobiocin and Rifampicin - Ramirez, Danyel; Berry, Liam; Domalaon, Ronald; Li, Yanqi; Arthur, Gilbert; Kumar, Ayush; Schweizer, Frank (Frontiers in Microbiology, 2021)
Recently reported peptidomimetics with increased resistance to trypsin were shown to sensitize priority multidrug-resistant (MDR) Gram-negative bacteria to novobiocin and rifampicin. To further optimize proteolytic stability, β-amino acid-containing derivatives of these compounds were prepared, resulting in three dioctanoyl ultrashort tetrabasic β-peptides (dUSTBβPs). The nonhemolytic dUSTBβP 3, comprised of three β3-homoarginine residues and two fatty acyl tails eight carbons long, enhanced the antibacterial activity of various antibiotics from different classes. Notably, compound 3 retained the ability to potentiate novobiocin and rifampicin in wild-type Gram-negative bacteria against MDR clinical isolates of Pseudomonas aeruginosa, Acinetobacter baumannii, Escherichia coli, Klebsiella pneumoniae, and Enterobacter cloacae. dUSTBβP 3 reduced the minimum inhibitory concentration of novobiocin and rifampicin below their interpretative susceptibility breakpoints. Furthermore, compound 3 exhibited improved in vitro stability (86.8 ± 3.7% remaining) relative to its α-amino acid-based counterpart (39.5 ± 7.4% remaining) after a 2 h incubation in human plasma.